2010
DOI: 10.1007/978-3-642-15745-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Skin-Liver Capsule Distance on Ultrasound RF Data for 1D Transient Elastography

Abstract: Abstract. Vibration-controlled transient elastography (VCTE™) technique is routinely used in clinical practice to assess non-invasively the liver stiffness which is correlated to hepatic fibrosis. Adequate use of the VCTE™ probe requires the knowledge of the distance between the skin and the liver parenchyma. This paper compares two methods to estimate this distance using spatial variations of the spectral content of ultrasound radiofrequency (RF) lines, obtained from a probe consisting of a single element ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…The thick layer of subcutaneous adiposity can account at least partially for the association between CAP and BMI. A previous study using the M probe also showed an independent association between BMI and CAP which still persisted in patients with steatosis less than 5% [18]. Overall, these data suggest the contribution of subcutaneous adipose tissue to CAP overestimation in patients with morbid obesity.…”
Section: Discussionsupporting
confidence: 64%
“…The thick layer of subcutaneous adiposity can account at least partially for the association between CAP and BMI. A previous study using the M probe also showed an independent association between BMI and CAP which still persisted in patients with steatosis less than 5% [18]. Overall, these data suggest the contribution of subcutaneous adipose tissue to CAP overestimation in patients with morbid obesity.…”
Section: Discussionsupporting
confidence: 64%
“…3 for three of the parameters, these images showed high spatial variations of the parameter values and poor homogeneity within the three tissue layers: subcutaneous fat, muscle/fat layer and liver. Segmentation of these layers might be worthwhile to investigate via three approaches: (1) thresholding of the RF envelope, which is limited by a high noise level and uncalibrated variations on the RF envelope intensity, (2) thresholding of the spectral variance, confirming the results reported in [12], (3) exploitation of the SPI converging to zero at specular interfaces between the three layers, as clearly observed in Fig. 3.…”
Section: Spectral Parametric Images For Tissue Segmentationsupporting
confidence: 75%
“…The SCD includes the layers of tissues connecting the epidermis of the skin to the liver, and can contain various proportions of fatty tissue. A fixed‐position FibroScan‐502 with M probe was used, and a series of temporal ultrasound radiofrequency lines were acquired to measure the subcutaneous layer thickness (<25 mm and ≥25 mm), which was subsequently separated from the liver tissue using real‐time computation during TE scanning . The value was based on the first measurement.…”
Section: Methodsmentioning
confidence: 99%
“…The layers of tissues that connect the skin to the liver capsule were defined as the skin capsular distance (SCD), and these layers are mainly comprised of subcutaneous fatty tissue. SCD may contribute to the beam distortion and scattering that is known to attenuate the propagation of shear waves into the liver and ultrasonic signals used to assess the speed of propagation . In patients with SCD thicker than 25 mm, the attenuation may be enhanced and lead to an overestimation of LSM, and the failure rate of the M probe was markedly increased to 33% .…”
mentioning
confidence: 99%